Proceedings of the ACM 2012 Conference on Computer Supported Cooperative Work 2012
DOI: 10.1145/2145204.2145285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of height visualizations for improving gestural communication at distributed tabletops

Abstract: In co-located collaboration, people use the space above the table for deictic gestures, and height is an important part of these gestures. However, when collaborators work at distributed tables, we know little about how to convey information about gesture height. A few visualizations have been proposed, but these have not been evaluated in detail. To better understand how remote embodiments can show gesture height, we developed several visualizations and evaluated them in three studies. First, we show that tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Genest et al [5] presented a technique for representing the height of a finger above a collaborative touch screen. However, their concentric circles visualization was not designed to be linearly mapped to the physical height, nor could it be used within the room surrounding the display surface.…”
Section: Related Workmentioning
confidence: 99%
“…Genest et al [5] presented a technique for representing the height of a finger above a collaborative touch screen. However, their concentric circles visualization was not designed to be linearly mapped to the physical height, nor could it be used within the room surrounding the display surface.…”
Section: Related Workmentioning
confidence: 99%
“…Most trace techniques, however, have only considered mouse movements rather than hand gestures (with Tang et al's work the notable exception [24]), and only show traces when in contact with the surface. Combining historical traces with height visualizations has been discussed [5], but only for telepointer-style embodiments.…”
Section: Enhancing Gesture Visibility In Distributed Settingsmentioning
confidence: 99%
“…Two exceptions are Fraser et al [4], who showed that representing approaches to a surface can improve distributed interactions, and Genest and Gutwin [5], who showed that abstract representations of height can improve gesture interpretation in distributed settings. Neither solution, however, captured detailed information about the hand and arm: Fraser captured the position of the tip of a stylus and Genest used a single 3D location, tracked with a magnetic-field sensor on the user's pointing finger.…”
Section: Capturing and Representing Gesture Heightmentioning
confidence: 99%
See 2 more Smart Citations